GENERAL CHARACTERISTICS OF THE ELEMENTS OF UPBRINGING IN TEACHING BIOLOGY - A. Semenov (Вестник Северо-Кавказского федерального университета)
One of the trends of modern education is the interaction of training and upbringing. Biology, as an academic subject, has a great upbringing potential. The elements of upbringing, the characteristics ofwhich are presented in this article, are defined by the draft federal state educational standard of basic general education of the third generation. For each element of upbringing, the definition, target, content, procedural and effective components that determine the nature of their course are indicated. Knowledge of the elements of upbringing will help teachers to better organize the educational process in biology, and methodologists to prepare future teachers for the implementation of the upbringing function.